2008
DOI: 10.1111/j.1479-8301.2008.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term reminiscence therapy on elderly with dementia: A comparison with everyday conversation approaches

Abstract: Background: Recent research has demonstrated the usefulness of reminiscence therapy as a psychosociological approach to the care of the demented elderly. However, to date neither the variables (e.g. evaluation methods and the optimal number of therapy sessions related to this technique) have been established, nor have the differences between reminiscence and other verbal interventions been clarified. In the field of clinical and nursing care in which reminiscence therapy is undertaken, in order to facilitate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 5 publications
(7 reference statements)
2
30
0
Order By: Relevance
“…There are several non‐pharmaceutical therapies for the elderly, including reminiscence therapy 13,14 and cognitive rehabilitation 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…There are several non‐pharmaceutical therapies for the elderly, including reminiscence therapy 13,14 and cognitive rehabilitation 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, reminiscence therapy among individuals with dementia is usually conducted in groups (Akanuma et al, 2011;Hsieh et al, 2010;Lalanne & Piolino, 2013;Wang, Yen, & OuYang, 2009). Studies about the use of reminiscence interventions found that it improves cognition (Akhoondzadeh, Jalalmanesh, & Hojjati, 2014;Cotelli et al, 2012;Tadaka & Kanagawa, 2007;Woods et al, 2005) decreases depressive symptoms (Chung, 2009;Hsieh et al, 2010;Wang, 2007), decreases behavioral symptoms (Akanuma et al, 2011;Hsieh et al, 2010;Huang, Li, Yang, & Chen, 2009;Wang et al, 2009;Woods et al, 2005;Yamagami, Oosawa, Ito, & Yamaguchi, 2007), promotes happiness (Okumura, Tanimukai, & Asada, 2008), enhances a positive mood (Cotelli et al, 2012;O´Rourke, Tobin, O´Callaghan, Sowman, & Collins, 2011;Woods et al, 2005) and facilitates communication (Huang et al, 2009;O´Rourke et al, 2011;Okumura et al, 2008).…”
Section: Reminiscence Therapy In Cognitive Declinementioning
confidence: 98%
“…The study was conducted in 4 different settings, with various routine activities equally available for both groups and so the only different intervention during this study was reminiscence sessions. Although some reminiscence studies opted to introduce a placebo intervention (e.g., Lai et al, 2004;Okumura et al, 2008;Serrani Azcurra, 2012), in our study design it would be difficult to perform an active intervention, such as social contact (Serrani Azcurra, 2012) in individual context, by the same therapist, without promoting reminiscence in the control group participants. For this reason, the reminiscence intervention was compared with a no treatment group, in line with previous investigations (Nakamae, Yotsumoto, Tatsumi, & Hashimoto, 2014;Woods et al, 2012).…”
Section: Reminiscence Interventionmentioning
confidence: 98%
“…Treatment of behavioral and psychological symptoms of dementia (BPSD) remains one of the most unmet needs in psychogeriatrics [7,8], with more effective pharmacological [9,10] and non-pharmacological interventions [11-13] needed. Psychogeriatrics is, however, a clinical subspecialty in which treatment should be directed towards the person as a whole.…”
Section: Introductionmentioning
confidence: 99%